ASPEK TADLIS PADA SISTEM JUAL BELI: Analisis pada Praktik Jual Beli Pulsa Listrik (Token) Prabayar - Alawi, M. Tholib (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
This article will illustrate about the electrical toys sale system (token) that occurred in society in modern times. Where it is found in the system of electricity toll transactions (token) today, after seen in practice there are aspects of tadlis on the transaction. Therefore, in this study will be described about the theory of the concept of the system of sale and purchase according to Islam and and aspects of tadlis in the sale and purchase transactions. Then do research through field observation. Analyzing the phenomenon that occurs in the field by referring to the theory that is loaded. As well as drawing conclusions by providing solutions of what has been studied. The type of this research is descriptive qualitative, population and sample determination in this research that is counter sales of electric pulse in Kota Cimahi kabupaten Bandung Barat Propinsi Jawa Barat. Data collection technique is done by observation, and data analysis technique is done through data reduction process, display data and verification. This study aims to reveal the aspects of tadlis in the sale and purchase of electrical pulses and provide solutions by providing electricity sales and purchase system in order to avoid the aspect of tadlis..Keywords: Jual Beli, Tadlis dan Pulsa Listrik (token)